1966
DOI: 10.1149/1.2424121
|View full text |Cite
|
Sign up to set email alerts
|

The Basic Significance of Oxygen Chemisorption on the Photoelectronic Properties of CdS and CdSe

Abstract: The long-known phenomenon of oxygen chemisorption on CdS and CdSe, more intensively studied recently, is shown to have a basic significance for the photoelectronic properties of thin crystals or layers. It is proposed that every "pure" crystal of CdS or CdSe is of relatively high conductivity [--~10 -6 (ohm cm) -1] and high photosensitivity (electron lifetime of 10 -3 sec) as prepared by standard techniques. If the crystal or layer is thin enough, oxygen adsorption obscures these properties and gives the appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1970
1970
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…The off-current is reduced dramatically aer air exposure; however, the overall current through the device also drops by several orders of magnitude and signicant hysteresis is apparent. This increase in resistivity is consistent with effects of oxygen adsorption on thin CdS lms previously observed by Bube, et al 31 and the observed depletion of electron density in CdS nanobelt devices upon exposure to oxygen. 32 These undesirable effects can be resolved by one nal annealing step at 300 C in a nitrogen atmosphere, leading to devices with reduced leakage currents and generally good performance.…”
supporting
confidence: 92%
“…The off-current is reduced dramatically aer air exposure; however, the overall current through the device also drops by several orders of magnitude and signicant hysteresis is apparent. This increase in resistivity is consistent with effects of oxygen adsorption on thin CdS lms previously observed by Bube, et al 31 and the observed depletion of electron density in CdS nanobelt devices upon exposure to oxygen. 32 These undesirable effects can be resolved by one nal annealing step at 300 C in a nitrogen atmosphere, leading to devices with reduced leakage currents and generally good performance.…”
supporting
confidence: 92%
“…In the experiments described here the minimum time bin was set to 100 ms, thereby limiting the accessible on'±off' kinetics to processes that occur on a longer time scale. [18] It is assumed that the adsorbed oxygen traps photogenerated electrons, which decreases the free-electron lifetime by a few orders of magnitude. Although this procedure is strictly valid only for exponential distributions, it still allows us to study the influence of oxygen on the blinking dynamics.…”
mentioning
confidence: 99%
“…Ground-state triplet oxygen is known to be an efficient fluorescence quencher via different mechanisms. [18] Obviously, the creation of additional traps by oxygen influences only the charging and not the neutralization and therefore leaves the off'-time distribution unaffected. [16] In another set of experiments it was suggested that the on'-times of flickering single terrylene-diimide (TDI) molecules were shortened by formation of a non-fluorescing TDI-oxygen complex.…”
mentioning
confidence: 99%
“…Obviously the presence of oxygen at the surface of the particles changes the electronic properties of the nanocrystals, which in turn changes their fluorescence behavior. In the past it has been shown, that adsorption of oxygen also changes the photoconductivity of thin CdS and CdSe films 29 . In this work the authors proposed that adsorbed oxygen can act as a scavenger for the charge carriers and therefore reduces the conductivity by more than one order of magnitude 30 .…”
Section: Resultsmentioning
confidence: 99%